Numerical simulation of the effects of simultaneous internal and external mass transfer resistances on the performance of the immobilized spherical catalyst pellet for Simple Michaelis-Menten Kinetics - Jameel, Ahmad Tariq; Hoda, Asif (Kulliyyah of Engineering International Islamic University Malaysia (IIUM) 50728 Kuala Lumpur Malaysia, 2017)
Immobilized biocatalysts have many advantages in large scale processing such as retention of enzyme or cell, enhanced stability and increased half-life of the enzyme [1] The efficiency of immobilized biocatalyst particles expressed by effectiveness factor play important role in the design and optimization of bioreactors. The effectiveness factor can be calculated once concentration profile within the catalyst pellet is obtained by solving the diffusion-reaction model. Complex rate kinetics such as given by Michaelis-Menten equation which represents host of biological reactions requires numerical solutions even for the simplest diffusion-reaction model. The diffusion-reaction model becomes even more involved in the presence of external mass transfer resistance which assumes significance as particle size increases. Different attempts at numerically solving nonlinear reaction-diffusion equation with and without external mass transfer effects have been reported in literature [1-4]. In this paper, we present a new approach based on finite difference method for the numerical simulation of nonlinear reaction-diffusion process in a spherical biocatalyst pellet with external film mass transfer resistance.